The Delivery of Extracellular Vesicles Loaded in Biomaterial Scaffolds for Bone Regeneration - Yan, Hui-Chun; Yu, Ting-Ting; Li, Jing; Qiao, Yi-Qiang; Wang, Lin-Chuan; Zhang, Ting; Li, Qian; Zhou, Yan-Heng; Liu, Da-Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Extracellular vesicles (EVs) are heterogeneous nanoparticles actively released by cells that comprise highly conserved and efficient systems of intercellular communication. In recent years, numerous studies have proven that EVs play an important role in the field of bone tissue engineering (BTE) due to several advantages, such as good biosafety, stability and efficient delivery. However, the application of EV therapies in bone regeneration has not been widely used. One of the major challenges for the application of EVs is the lack of sufficient scaffolds to load and control the release of EVs. Thus, in this review, we describe the most advanced current strategies for delivering EVs with various biomaterials for use in bone regeneration, the role of EVs in bone regeneration, the distribution of EVs mediated by biomaterials and common methods of promoting EV delivery efficacy with a focus on biomaterial properties.